Socialisation of Technology Education in the Aviation World for High School Students: Sosialisasi Edukasi Teknologi di Dunia Penerbangan Bagi Pelajar Sekolah Menengah Atas - Fauziah Nur; Inda Tri Pasa; Ivana Wardani; Catra Indra Cahyadi; Rini Sadiatmi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Technological developments are increasingly developing, especially in the world of aviation. Therefore, aviation vocational institutions provide sources of knowledge and technology that can be implemented in several ways, including by carrying out community service activities related to aviation technology. Currently, the aerospace insight possessed by the community is still limited, especially for students of SMA Negeri 1 Tanjung Morawa. This PkM activity aims to provide education to the community as basic capital to increase aerospace insight needed by the job market in the aviation sector. The method used in this activity is counselling by providing material about technology in the world of aviation. The results of this activity show that students of SMA Negeri 1 Tanjung Morawa experienced an increase in knowledge about technology in the world of aviation, as evidenced by the percentage of participant posttests of 85% for increased scores and 0% for decreased scores. From this counselling, it can be concluded that participants can gain new knowledge about aviation technology from the implementation of this activity.